Tethered Agonist Analogs as Site-Specific Probes for Domains of the Human α7 Nicotinic Acetylcholine Receptor that Differentially Regulate Activation and Desensitization - Wang, Jingyi (The American Society for Pharmacology and Experimental Therapeutics, 2010)
Homomeric α7 nicotinic acetylcholine receptors represent an important and complex pharmaceutical target. They can be activated by structurally diverse agonists and are highly likely to enter and remain in desensitized states at rates determined by the structures of the agonists. To identify structural elements regulating this function, we introduced reactive cysteines into the α7 ligand-binding domain allowing us to bind sulfhydryl-reactive (SH) agonist analogs or control reagents onto specific positions in the ligand binding domain. We identified four α7 mutants (S36C, L38C, W55C, and L119C) in which the tethering of the SH reagents blocked further acetylcholine-evoked activation of the receptor. However, after selective reaction with SH agonist analogs, the type II allosteric modulator N-(5-chloro-2,4-dimethoxyphenyl)-N′-(5-methyl-3-isoxazolyl-3-isoxazolyl)-urea (PNU-120596) could reactivate L119C and W55C mutants and receptors with a reduced or modified C-loop. Modified S36C and L38C mutants were insensitive to reactivation by PNU-120596, whether they were reacted with agonist analogs or alternative SH reagents. Molecular modeling showed that in the W55C and L119C mutants, the ammonium pharmacophore of the agonist analog methanethiosulfonate-ethyltrimethylammonium would be in a similar but nonidentical position underneath the C-loop. The orientation assumed by the ligand tethered to 119C was approximately 3-fold more sensitive to PNU-120596 than the alternative pose at 55C. Our results support the hypothesis that a single ligand can bind within the receptor in different ways and, depending on the specific binding pose, may variously promote activation or desensitization, or, alternatively, function as a competitive antagonist. This insight may provide a new approach for drug development.